Cytotoxic activity of the twigs of Cinnamomum cassia through the suppression of cell proliferation and the induction of apoptosis in human colorectal cancer cells - Gwang Hun Park; Hun Min Song; Su Bin Park; Ho-Jun Son; Yurry Um; Hyun-Seok Kim; Jin Boo Jeong (BMC, 2018)
Abstract Background Because twigs of Cinnamomum cassia (TC) have been reported to exert anti-cancer activity, the mechanistic study for TC's anti-cancer activity is required. Thus, we elucidated the potential molecular mechanism of TC's anti-proliferative effect and the induction of apoptosis in human colorectal cancer cells. Methods How water extracts form TC (TC-HW) was used in this study. Anti-cell proliferative effect of TC-HW was evaluated by MTT assay. The change of protein or mRNA level by TC-HW was evaluated by Western blot and RT-RCR, respectively. The promoter construct for ATF3, NF-κB, TOP-FLASH or FOP-FLASH was used for the investigation of the transcriptional activity for ATF3, NF-κB or Wnt. siRNA for ATF3 or p65 was used for the knockdown of ATF3 and p65. Results TC-HW reduced the cell viability in human colorectal cancer cells. TC-HW decreased cyclin D1 protein level through cyclin D1 degradation via GSK3β-dependent threonine-286 (T286) phosphorylation of cyclin D1, indicating that cyclin D1 degradation may contribute to TC-HW-mediated decrease of cyclin D1 protein level. TC-HW downregulated the expression of cyclin D1 mRNA level and inhibited Wnt activation through the downregulation of β-catenin and TCF4 expression, indicating that inhibition of cyclin D1 transcription may also result in TC-HW-mediated decrease of cyclin D1 protein level. In addition, TC-HW was observed to induce apoptosis through ROS-dependent DNA damage. TC-HW-induced ROS increased NF-κB and ATF3 activation, and inhibition of NF-κB and ATF3 activation attenuated TC-HW-mediated apoptosis. Conclusions Our results suggest that TC-HW may suppress cell proliferation through the downregulation of cyclin D1 via proteasomal degradation and transcriptional inhibition, and may induce apoptosis through ROS-dependent NF-κB and ATF3 activation. These effects of TC-HW may contribute to the reduction of cell viability in human colorectal cancer cells. From these findings, TC-HW has potential to be a candidate for the development of chemoprevention or therapeutic agents for human colorectal cancer.